2013
DOI: 10.5851/kosfa.2013.33.6.763
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Changes during Freezing and Effect of Physicochemical Properties after Thawing on Meat by Air Blast and Magnetic Resonance Quick Freezing

Abstract: This study was carried out to investigate the effects of various temperatures of electro-magnetic resonance and air blast freezing methods on the physicochemical quality of meat. Beef (loin and round), pork (belly and ham) and chicken (breast and leg) were purchased at a commercial market, and the meat was frozen using three methods: air blast freezing (-20 o C and -45 o C) and electro-magnetic resonance quick freezing. Changes in the physicochemical properties of meat were analyzed by drip loss, cooking loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
(2 reference statements)
2
12
1
Order By: Relevance
“…Even though the freezing rates achieved in each device were very different, the authors only found minor differences among the samples. By contrast, Kim et al (2013a), Kim et al (2013b), Ku et al (2014), and Choi et al (2015) froze beef, pork, and chicken samples in both a CAS freezer at −55 °C and an air-blast freezer at −45 °C. They concluded that electromagnetic freezing reduced the total freezing times and preserved the quality attributes of the samples better than air-blast freezing.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Even though the freezing rates achieved in each device were very different, the authors only found minor differences among the samples. By contrast, Kim et al (2013a), Kim et al (2013b), Ku et al (2014), and Choi et al (2015) froze beef, pork, and chicken samples in both a CAS freezer at −55 °C and an air-blast freezer at −45 °C. They concluded that electromagnetic freezing reduced the total freezing times and preserved the quality attributes of the samples better than air-blast freezing.…”
Section: Introductionmentioning
confidence: 93%
“…To avoid this inconvenience, some authors have compared the quality of several foods frozen in both commercial electromagnetic freezers and conventional devices (Choi, Ku, Jeong, Jeon, & Kim, 2015;Erikson et al, 2016;Kim et al, 2013b;Yamamoto, Tamura, Matsushita, & Ishimura, 2005). Unfortunately, the few existing studies provide little or no information about the characteristics of the magnetic fields applied.…”
Section: Introductionmentioning
confidence: 99%
“…In the claimed patent, AEF generated by a radio frequency voltage prevented freezing of foods at above − 5 °C (minimum allowable supercooling temperature). It is likely that the applied AEF continuously vibrated, rotated, and translated water molecules due to the polarity of the molecules and these actions maintained the supercooled state of water without crystallization (Kim et al, 2013b ). In this sense, Ma et al (2013) confirmed that the degree of supercooling in 0.9% NaCl aqueous solution was enhanced by an AC electric field (100 kV/m at 10 6 Hz) due to the induced electric dipole oscillation.…”
Section: Experimental Studies: the Effects Of Aef On Freezingmentioning
confidence: 99%
“…Using a "copy" of the ABI, CAS system reported that they had found that oscillating weak magnetic fields had no affect on the freezing curves of sweet potato, spinach, fish, agar gel, or water and had no visible effect on cellular microstructures of the tissues they examined. Kim et al (2013) have reported faster freezing and lower drip losses in some meats when using magnetic resonance freezing but increased cooking losses. However, they do not appear to have compared like with like.…”
Section: Magnetic Resonance-assisted Freezing (Mraf)mentioning
confidence: 99%